Quaternary dating by electron spin resonance (ESR) applied to human tooth enamel - Carvajal Eduar; Montes Luis; Almanza Ovidio A. (Earth Sciences Research Journal)
This paper presents the results obtained from using electron paramagnetic resonance (EPR) to analyse tooth enamel found at the Aguazuque archaeological site (Cundinamarca, Colombia), located on the savannah near Bogota at 4° 37' North and 74°17' West. It was presumed that the tooth enamel came from a collective burial consisting of 23 people, involving men, women and children. The tooth enamel was irradiated with gamma rays and the resulting free radicals were measured using an electron spin resonance (ESR) X-band spectrometer to obtain a signal intensity compared to absorbed doses curve. Fitting this curve allowed the mean archaeological dose accumulated in the enamel during the period that it was buried to be estimated, giving a 2.10 ± 0.14 Gyvalue. ROSY software was used for estimating age, giving a mean 3,256 ± 190y before present (BP) age. These results highlight EPR's potential when using the quaternary ancient ruins dating technique in Colombia and its use with other kinds of samples like stalagmites, calcite, mollusc shells and reefs.